2020
DOI: 10.1002/batt.202000141
|View full text |Cite
|
Sign up to set email alerts
|

One‐Step Synthesis of Porous Ni−Co−Fe−S Nanosheet Arrays as an Efficient Battery‐Type Electrode Material for Hybrid Supercapacitors

Abstract: Construction of porous nanosheet arrays of transition-metal sulfides (TMSs) holds great potential for energy storage. Herein, a one-step hydrothermal process is employed for the construction of porous Ni 1.43 Fe .5 Co .5 S .97 nanosheet arrays (NFCS-NS) on the nickel foam as a proper positive electrode for hybrid supercapacitor. Owing to the appealing structural features, the NFCS-NS depicts a high capacity of 1156 C g À 1 at 2 A g À 1 , desirable rate capability of 81.1 %, and significant cyclability of 92.9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…The CVs recorded for P@Bi 2 Se 3 /NF electrode at different scan rates from 2 to 50 mV s À 1 display the retention of signature redox peaks with intactness of shape and battery like behavior even at higher scan rate. [68] The GCD behavior of P@Bi 2 Se 3 recorded at various current densities (3,4,6,8,10,12,15, 18 and 20 A g À 1 ) are shown in Figure 4(f) and it is observed that all the GCD curves are symmetric in nature and nonlinear while, upon increasing the current densities, the discharge times decreases. At high current densities the charge/discharge process occurs much faster than at low current densities.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The CVs recorded for P@Bi 2 Se 3 /NF electrode at different scan rates from 2 to 50 mV s À 1 display the retention of signature redox peaks with intactness of shape and battery like behavior even at higher scan rate. [68] The GCD behavior of P@Bi 2 Se 3 recorded at various current densities (3,4,6,8,10,12,15, 18 and 20 A g À 1 ) are shown in Figure 4(f) and it is observed that all the GCD curves are symmetric in nature and nonlinear while, upon increasing the current densities, the discharge times decreases. At high current densities the charge/discharge process occurs much faster than at low current densities.…”
Section: Resultsmentioning
confidence: 94%
“…Furthermore, their significant features such as wide range of bandgap with tunability, optical absorption in longer wavelength, [4–7] localized magnetic moments, [4,8,9] and layered structures influenced anisotropic properties and their competence to accommodate host species thorough intercalation, make them preferable [10] . Layered transition‐metal chalcogenides are a class of materials which comprise of metals such as Mo, Co and chalcogens (X) such as S, Se and Te [11,12] . The metal atoms are sandwiched by covalent bonds in between a pair of chalcogen atoms to form quintuple layer (Se−Bi−Se−Bi‐Se) and the individual layers are held together via ‘van der Waals’ forces [13] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the hybrid device could retain an energy density of 6.3 Wh Kg À 1 at a high power density of 15725 W kg À 1 . The energy density values achieved from our carbon paper supported hybrid device are comparable to few nickel foam supported hybrid devices, such as Co 3 O 4 //AC (22.5 Wh Kg À 1 at 800 W kg À 1 ), [21] and Ni 3 S 4 //AC (18.5 Wh Kg À 1 at 1500 W kg À 1 ), [27] whereas the values are still lower compared to CuCo 2 O 4 //AC (40 Wh Kg À 1 at 944 W kg À 1 ), [22] NiVLDH//AC (30.6 Wh Kg À 1 at 780 W kg À 1 ), [60] NiCoFeS//AC (57.3 Wh Kg À 1 at 807 W kg À 1 ), [61] and NiCoSe 2 @NiMnLDH//AC (47 Wh Kg À 1 at 810 W kg À 1 ). [62] The decent energy density of carbon paper supported NS-15E(1)//AC hybrid could be attributed to the high specific capacity of network like NS-15E(1) and a wide voltage window of 0-1.6 V. Further, the hybrid device showed good capacitive retention of 70 % even after 3000 cycles along with an excellent 99 % Columbic efficiency (Figure 6f).…”
Section: Chemelectrochemmentioning
confidence: 96%
“…The binding energy of 2p 1/2 at 794.5 eV and 2p 3/2 at 779.1 eV correspond to Co 3+ , the peaks of 799.8 eV of 2p 1/2 and 783.6 eV of 2p 3/2 belong to Co 2+ and the other two vibrational companion peaks are at 804.4 and 787.7 eV. 33,34 This reflects that Co also exists as Co 3+ and Co 2+ . As shown in Figure 3e, the spectrum of S 2p has two peaks corresponding to the S 2p 3/2 and 2p 1/2 orbitals of S at binding energies of 162.9 and 164.3 eV, respectively.…”
Section: Introductionmentioning
confidence: 99%